1999
DOI: 10.1002/(sici)1520-6777(1999)18:1<55::aid-nau8>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Altered bladder function in transgenic mice expressing rat elastin

Abstract: The elasticity of tissues subjected to repeated deformation is provided by the presence of elastic fibers in the extracellular matrix (ECM). The most abundant component of elastic fibers is elastin, whose soluble precursor is tropoelastin. To establish the role elastin plays in the bladder, this study describes the biosynthetic, histologic, and physiologic consequences of expression of an isoform of rat tropoelastin in transgenic mouse bladder. The polymerase chain reaction (PCR) was used to determine expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The viscoelastic properties of the bladder are primarily dependent on the elements contained within the extracellular matrix (4, 64). Elastin, for example, is very compliant compared with collagen (32,45). Elastin contributes mainly to the foot of the passive length-tension curve, while the sharp rising portion reflects the collagen component.…”
Section: Resultsmentioning
confidence: 99%
“…The viscoelastic properties of the bladder are primarily dependent on the elements contained within the extracellular matrix (4, 64). Elastin, for example, is very compliant compared with collagen (32,45). Elastin contributes mainly to the foot of the passive length-tension curve, while the sharp rising portion reflects the collagen component.…”
Section: Resultsmentioning
confidence: 99%
“…In animal models, Lemack et al. [7] found increased bladder compliance in transgenic mice overexpressing rat‐elastin compared with their non‐transgenic littermates. Conversely, mice with the same genotype as in this study were found to develop hypertension [19], possibly through the mechanism that the aorta and arteries of elastin‐deficient mice become less distensible (reduced compliance), leading to higher blood pressure during systole.…”
Section: Discussionmentioning
confidence: 99%
“…Elements of the ECM are believed to determine the visco-elastic properties of the bladder [ 14,15 ] . In particular, collagen is thought to provide tensile strength, whereas elastin probably enhances tissue compliance [ 7 ] . In the present study, we found that Eln + / − mice, with approximately one-third less bladder elastin and no signifi cant change in collagen content, had signifi cantly decreased bladder compliance and capacity compared with Wt controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is the case in other tissues, deficient or aberrant elastic fiber formation and matrix deposition affects bladder function [368, 369, 373]. Excess levels of CS and dermatan sulfate have been implicated in downregulating elastin secretion by bladder fibroblasts [374, 375].…”
Section: Progress Towards Engineering/regenerating Tissue-type-specifmentioning
confidence: 99%